Preparation method and interconnection process of carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service
By depositing silver shell layers on carbon nanospheres to form carbon nanospheres @Ag core shell materials, the problems of poor stability and high cost of nanoAg particles at high temperatures are solved, and low-temperature connection, high-temperature service and cost reduction are achieved The effect is suitable for the manufacturing of semiconductor devices.
Patent Information
- Application Number
- CN202310314041.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-03-28
AI Technical Summary
Traditional chip packaging interconnect materials are difficult to operate stably at high temperatures, and nano-Ag particles are costly and easily lead to electromigration and chemical migration, affecting product reliability. However, carbon nanoparticles lack connectivity and are difficult to be applied in the connection field.
The preparation method of carbon nanospheres @Ag core shell material is used to prepare hollow carbon nanospheres by micelle-interface copolymerization and carbon thermal reduction, and a silver shell layer is deposited on its surface to form carbon nanospheres @Ag core shell material. The hollow structure improves the mobility and connectivity of silver and reduces the sintering temperature.
It realizes the effect of low-temperature connection and high-temperature service, reduces sintering temperature, improves the material's oxidation resistance and shear resistance, reduces costs, and maintains long-term stability at high temperatures. It is suitable for the manufacturing of semiconductor devices and microelectronics. Package.
Smart Images

Figure CN116275028B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electronic packaging micro-interconnection, and relates to a chip packaging interconnection material, and specifically to a preparation method and interconnection process of a carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service. Background Art
[0002] Research shows that devices made from third-generation semiconductors are favored by new energy vehicles, 5G, ultra-high voltage, data centers, and other fields due to their advantages such as high voltage resistance, high temperature resistance, high power, radiation resistance, strong conductivity, high operating speed, and low operating loss. However, due to their high operating temperature of 250°C to 300°C, traditional chip packaging interconnect materials are difficult to meet the conditions for their high-temperature service, and new alternative materials are urgently needed. However, due to the nano-size effect of metal nanoparticles, the sintering process does not pass through the liquidus, and the sintering temperature can be far lower than the melting point of the bulk. At the same time, after sintering, nanomaterials can operate stably and for a long time at higher temperatures, which well meets the requirements of "low-temperature sintering and high-temperature service" and is an ideal chip interconnect material.
[0003] Nano-Ag particles have low sintering temperatures, high service temperatures, and excellent electrical and thermal conductivity, as well as strong corrosion and oxidation resistance. However, silver nanoparticles are expensive and subject to severe electromigration and chemical migration, which can lead to circuit short-circuit failures and severely impact product reliability. Carbon nanoparticles offer excellent conductivity, low cost, and stable properties, but due to their inherent lack of connectivity, they are rarely used in the connection field. Summary of the Invention
[0004] In response to the above-mentioned problems existing in the field of connection between existing nano-Ag and carbon nanomaterials, the present invention provides a preparation method and interconnection process of carbon nanosphere@Ag core-shell materials for low-temperature connection and high-temperature service. The structural characteristics of the inner core carbon and the outer shell Ag can give full play to the advantages of both materials. The hollow carbon core can improve the anti-migration property of silver and reduce the cost of interconnection materials. It absorbs external stress and relieves local stress concentration through deformation; the nanoscale Ag shell provides good connectivity, significantly reduces the sintering temperature, and has good oxidation resistance.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service comprises the following steps:
[0007] Step 1: Preparation of hollow carbon nanosphere materials
[0008] In this step, the preparation method of hollow carbon nanospheres is the existing technology, which is prepared by micelle-interfacial copolymerization and carbothermal reduction. The specific preparation method is as follows:
[0009] Step 1.1, adding organic monomers aniline and pyrrole to an aqueous solution containing an amphiphilic surfactant, adding a tin oxide colloidal solution, stirring and ultrasonically dispersing for 30 to 120 minutes to obtain a uniform mixed solution, wherein:
[0010] The dosage ratio of pyrrole and aniline is 1.125-0.500 mL:1 mL;
[0011] The amphiphilic surfactant is polyethylene glycol octylphenyl ether (TritonX-100), and the ratio of the total amount of pyrrole and aniline is 1g:7.3-15.0mL;
[0012] The ratio of the total amount of pyrrole and aniline to the water in the aqueous solution of the amphiphilic surfactant is 0.8-3.2 mg:1 g;
[0013] The ratio of the amount of tin oxide colloid to the water in the aqueous solution of the amphiphilic surfactant is 5-15 mg:1 g;
[0014] Step 1.2: Place the mixed solution in an ice-water bath and stir for 20 to 60 minutes, add the initiator aqueous solution and stir vigorously for 20 to 50 seconds, and then react at 0 to 6°C for 12 to 36 hours. The obtained product is washed and dried to obtain a hollow carbon nanosphere material precursor, wherein:
[0015] The initiator in the initiator aqueous solution is ammonium persulfate, and the ratio of ammonium persulfate to the total amount of pyrrole and aniline is 1.00-6.27 g:1 mL;
[0016] The initiator aqueous solution is pre-cooled to 0-5°C before addition;
[0017] The washing refers to washing the product with deionized water multiple times and filtering under reduced pressure until the filtrate is close to neutral;
[0018] Step 1.3: subjecting the hollow carbon nanosphere material precursor to high-temperature carbonization treatment to obtain the hollow carbon nanosphere material, wherein:
[0019] The high-temperature carbonization treatment is to heat the material to 600-1000°C at a heating rate of 2-10°C / min in an inert atmosphere and carbonize the material for 3-20 hours;
[0020] Step 2: Preparation of carbon nanospheres@Ag core-shell materials
[0021] Step 2.1: Disperse the hollow carbon nanospheres obtained in step (1) in a solvent, stir and ultrasonically treat for 20 to 40 minutes, wherein:
[0022] The solvent is selected from one or more of water, ethanol, and polyethylene glycol;
[0023] The ratio of the amount of the hollow carbon nanospheres to the solvent is 0.00025-0.0005 g:1 mL;
[0024] Step 2.2: Add a silver source, stir for 20 to 40 minutes in the dark, and then add a reducing agent, wherein:
[0025] The silver source is a diammine silver nitrate solution with a concentration of 0.0125 mol / L, and the ratio of the diammine silver nitrate solution to the solvent used to disperse the hollow carbon nanospheres is 1-2 mL:1 mL;
[0026] The reducing agent is polyvinyl pyrrolidone, and the ratio of polyvinyl pyrrolidone to hollow carbon nanospheres is 10-20g:1g;
[0027] Step 2.3, stirring the solution obtained in step 2.2 at room temperature in the dark for 8 to 24 hours;
[0028] Step 2.4: Wash, centrifuge, and redisperse the product obtained in step 2.3 multiple times, and then dry it to obtain a carbon nanosphere@Ag core-shell material. The carbon nanosphere@Ag core-shell material can be used in the field of electronic packaging micro-interconnection technology.
[0029] A process for interconnecting carbon nanospheres@Ag core-shell materials prepared by the above method comprises the following steps:
[0030] Step 1: Substrate processing
[0031] Step 1.1: Use acetone to remove oil stains on the substrate surface, and use dilute hydrochloric acid to remove surface oxides;
[0032] Step 1.2: After drying, polish the substrate cleaned in step 1.1 to further remove the surface oxide film;
[0033] Step 1.3: Place the substrate treated in step 1.2 in a vacuum drying oven and store it at room temperature under a vacuum condition of -1 MPa;
[0034] Step 2: Preparation and application of solder paste
[0035] Step 2.1: Place the carbon nanosphere@Ag core-shell material in a mortar, add an organic dispersant, and grind thoroughly to mix evenly and grind into a paste to obtain a carbon nanosphere@Ag core-shell solder paste, wherein:
[0036] The organic dispersant may be one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol;
[0037] The mass percentage of the mixed powder and the organic dispersant in the solder paste is 80-90%:10-20%;
[0038] Step 2.2: evenly apply the carbon nanosphere@Ag core-shell solder paste on the substrate processed in step 1 by screen printing, wherein:
[0039] The coating thickness of the carbon nanosphere@Ag core-shell material solder paste on the substrate is 50 to 200 μm;
[0040] Step 2.3: Place the solder paste coated substrate in a constant temperature drying oven and preheat at 110-140°C for 5-30 minutes to remove some of the residual anhydrous ethanol in the solder paste to avoid the formation of more pores in the sintered structure.
[0041] Step 3: Hot pressing and sintering
[0042] The chip is placed on the solder paste to form a sandwich structure, and then placed in a hot press for hot pressing and sintering.
[0043] The hot pressing sintering adopts double-sided heating, with a temperature rise rate of 4-10° C. / min, a pressure of 1-10 MPa, a heating temperature of 250-350° C., and a heating time of 5-60 min.
[0044] Compared with the prior art, the present invention has the following advantages:
[0045] 1. Hollow carbon nanospheres are produced by interfacial copolymerization and carbothermal reduction. Compared to the template method, the process is simpler and the cost is lower than that of pure Ag nanoparticle solder paste. Hollow carbon nanospheres can increase the barrier to silver ion migration, improving silver's resistance to migration. Furthermore, hollow carbon nanospheres can absorb external stress through plastic deformation, thereby alleviating localized stress concentration and improving the shear resistance of the weld.
[0046] 2. Tin oxide colloid is added during the preparation of hollow carbon nanospheres. After subsequent carbothermal reduction, it is reduced to elemental tin. The tin element enters the pores of the carbon nanosphere shell through melt filling, improving the material's conductivity and strengthening the bonding between the silver shell and the carbon nanosphere in the subsequent electroless plating process.
[0047] 3. The diameter of the carbon nanosphere@Ag core-shell particles is 100-150nm. Due to the nano-size effect, the sintering process does not pass through the liquidus, and the sintering temperature can be far below the melting point of bulk Ag. At the same time, after sintering, the nanomaterial can operate stably at higher temperatures for a long time.
[0048] 4. The carbon nanosphere@Ag core-shell material of this invention exhibits excellent oxidation resistance, effectively reducing pores and holes in the joints formed through plastic deformation. Furthermore, it enables "low-temperature connection and high-temperature service." Plastic deformation of the nanoparticles effectively reduces pores and holes in the joints formed, enabling the interconnection of chips and substrates at low temperatures, completing the connection and packaging of semiconductor devices. Therefore, this invention is well-suited for applications in semiconductor device manufacturing, microelectronics packaging, power electronics packaging, and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Schematic diagram of the structure of the carbon nanosphere@Ag core-shell material prepared in Example 2;
[0050] Figure 2 Schematic diagram of sintering using printed carbon nanospheres@Ag core-shell solder paste;
[0051] Figure 3 Transmission electron microscopy (TEM) images and energy dispersive spectrometry (EDS) spectra of the hollow carbon nanospheres prepared in Example 1;
[0052] Figure 4 Transmission electron microscope (TEM) images and energy dispersive spectrometer (EDS) diagrams of the carbon nanosphere@Ag core-shell particles prepared in Example 2. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below with reference to the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the scope of protection of the present invention.
[0054] Example 1: Preparation of hollow carbon nanospheres
[0055] Take 0.49 mL of aniline and 0.38 mL of pyrrole, add them to 60 mL of an aqueous solution containing TritonX-100 (0.06 g), add 5 mL of an aqueous solution containing 0.6 g of tin oxide colloid, stir and ultrasonically disperse to obtain a uniform mixed solution; then place the mixed solution in an ice water bath and stir for 30 minutes, add 5 mL of an aqueous solution containing 2.47 g of ammonium persulfate, stir vigorously for 30 seconds, and then react at 0-6 ° C for 24 hours. The obtained product is washed with deionized water and ethanol, filtered until the filtrate is colorless and transparent, and dried to obtain a precursor of a hollow carbon nanosphere material; the above-mentioned hollow carbon nanosphere material precursor is placed in a tube furnace, heated to 700 ° C at a heating rate of 5 ° C / min under nitrogen protection, and carbonized for 3 hours to obtain a hollow carbon nanosphere material, the transmission electron microscope (TEM) photo and energy spectrum (EDS) are as shown. Figure 3 As shown. Figure 3It can be clearly seen that the hollow carbon nanosphere material prepared in this example has a hollow structure with uniform size, and the tin element is uniformly dispersed inside the carbon shell.
[0056] Example 2: Preparation of carbon nanospheres@Ag core-shell materials
[0057] The hollow carbon nanospheres (0.05 g) obtained in Example 1 were dispersed in 100 mL of solvent, stirred and ultrasonically treated for 30 min, wherein the solvent was selected from one or more of water, ethanol, and polyethylene glycol. 30 mL of diammine silver nitrate solution (concentration of 0.0125 mol / L) was added, stirred for 30 min under light-proof conditions, and then 10 mL of an aqueous solution containing 0.15 g of polyvinyl pyrrolidone was added, and the resulting solution was stirred for 12 h under light-proof conditions at room temperature. The resulting product was washed, centrifuged, and redispersed several times, and then dried to obtain a carbon nanosphere @Ag core-shell material, the structural schematic of which is shown in FIG. Figure 1 As shown in the transmission electron microscope (TEM) and energy dispersive spectrometer (EDS) Figure 4 As shown. Figure 4 It can be clearly seen that the carbon nanosphere@Ag core-shell material prepared in this embodiment exhibits a spherical structure with an irregular surface, the silver element covers the surface of the sphere and presents an irregular morphology, and the tin element is evenly dispersed inside the sphere.
[0058] Example 3: Preparation and application of solder paste
[0059] The carbon nanosphere @Ag core-shell material prepared in Example 2 is placed in a mortar, an appropriate amount of polyethylene glycol-400 is added, and the mixture is thoroughly ground to form a paste, whereby the mixture is evenly mixed and ground into a paste to obtain a carbon nanosphere @Ag core-shell solder paste, wherein the mass percentage of the mixed powder and the organic dispersant in the solder paste is 85%:15%; the substrate is surface treated, acetone is used to remove oil stains on the surface of the substrate, and dilute hydrochloric acid is used to remove surface oxides; after drying, the cleaned substrate is polished to further remove the surface oxide film; the treated substrate is placed in a vacuum drying oven and stored at room temperature; the carbon nanosphere @Ag core-shell solder paste is evenly coated on the treated substrate by screen printing, wherein the coating thickness of the carbon nanosphere @Ag core-shell material solder paste on the substrate is 80 μm; the substrate coated with the solder paste is placed in a constant temperature drying oven and preheated at 140°C for 10 minutes to remove some of the residual anhydrous ethanol in the solder paste to avoid the formation of more pores in the sintered structure.
[0060] Example 4: Hot Pressing Sintering
[0061] like Figure 2As shown, the chip is placed on the carbon nanosphere @ Ag core-shell solder paste of Example 3 to form a sandwich structure, and placed in a hot press for hot pressing and sintering, wherein: the heating method adopts double-sided heating, the temperature rise rate is 5°C / min, the pressure is 10 MPa, the heating temperature is 300°C, and the heating time is 30 min.
[0062] Example 5: Interconnection Process with Different Solder Paste Coating Thicknesses
[0063] The difference between this embodiment and embodiment 3 is that the coating thickness of the carbon nanosphere@Ag core-shell material solder paste on the substrate is changed to 50 μm and 100 μm, and then hot pressing sintering is performed according to the same procedure as embodiment 4.
[0064] Example 6: Hot Pressing Sintering Processes with Different Temperature Rise Rates
[0065] The difference between this embodiment and embodiment 4 is that the temperature rise rate of the carbon nanosphere@Ag core-shell material solder paste during sintering is changed to 10° C. / min.
[0066] Example 7: Hot Pressing Sintering Process at Different Sintering Pressures
[0067] The difference between this embodiment and embodiment 4 is that the pressure of the carbon nanosphere@Ag core-shell material solder paste during sintering is changed to 1 MPa and 5 MPa respectively.
[0068] Example 8: Hot Pressing Sintering Process at Different Heating Temperatures
[0069] The difference between this embodiment and embodiment 4 is that the sintering temperatures of the carbon nanosphere@Ag core-shell material solder paste are changed to 250° C. and 350° C., respectively.
[0070] Example 9: Hot Pressing Sintering Process with Different Heating Times
[0071] The difference between this embodiment and embodiment 4 is that the holding time of the carbon nanosphere@Ag core-shell material solder paste during sintering is changed to 5 min, 10 min, 20 min, 40 min and 60 min.
Claims
1. A method for preparing a carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service, characterized in that The method comprises the following steps: Step 1, dispersing the hollow carbon nanospheres in a solvent, stirring and ultrasonically treating, wherein: the ratio of the amount of the hollow carbon nanospheres to the solvent is 0.00025-0.0005 g: 1 mL, and the hollow carbon nanosphere material is prepared by micelle-interfacial copolymerization and carbon thermal reduction. The specific preparation method is as follows: Step (1) adding organic monomers aniline and pyrrole to an aqueous solution containing an amphiphilic surfactant, adding a tin oxide colloidal solution, stirring and ultrasonically dispersing, to obtain a uniform mixed solution, wherein: the amount ratio of the pyrrole to the aniline is 1.125-0.500 mL: 1 mL; the ratio of the amphiphilic surfactant to the total amount of pyrrole and aniline is 1 g: 7.3-15.0 mL; the ratio of the total amount of pyrrole and aniline to the water in the aqueous solution of the amphiphilic surfactant is 0.87 mL: 60 mL; the ratio of the amount of the tin oxide colloidal to the water in the aqueous solution of the amphiphilic surfactant is 5-15 mg: 1 g; Step (2) placing the mixed solution in an ice water bath and stirring, adding an initiator aqueous solution and stirring vigorously, and then reacting at 0-6°C, washing and drying the obtained product to obtain a hollow carbon nanosphere material precursor, wherein: the ratio of the initiator to the total amount of pyrrole and aniline is 1.00-6.27 g: 1 mL; Step (3) subjecting the hollow carbon nanosphere material precursor to high temperature carbonization treatment to obtain the hollow carbon nanosphere material; Step 2, adding a silver source, stirring under light-proof conditions, and then adding a reducing agent, wherein: the ratio of the amount of the silver source to the solvent used to disperse the hollow carbon nanospheres is 1-2 mL: 1 mL; the ratio of the amount of the reducing agent to the amount of the hollow carbon nanospheres is 10-20 g: 1 g; Step 3, stirring the solution obtained in step 2 at room temperature in the dark; Step 4: The product obtained in step 3 is washed, centrifuged, and redispersed for multiple times, and then dried to obtain a carbon nanosphere@Ag core-shell material.
2. The method for preparing the carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service according to claim 1, characterized in that The amphiphilic surfactant is polyethylene glycol octylphenyl ether; the initiator is ammonium persulfate; the initiator aqueous solution is pre-cooled to 0-5°C before adding; the high-temperature carbonization treatment is to heat the temperature to 600-1000°C at a heating rate of 2-10°C / min in an inert atmosphere and carbonize for 3-20 hours.
3. The method for preparing the carbon nanosphere@Ag core-shell material for low-temperature connection and high-temperature service according to claim 1, characterized in that The solvent is selected from one or more of water, ethanol and polyethylene glycol; the silver source is diammine silver nitrate solution with a concentration of 0.0125 mol / L; and the reducing agent is polyvinyl pyrrolidone.
4. A process for interconnecting carbon nanospheres@Ag core-shell materials prepared by the method according to any one of claims 1 to 3, characterized in that The process comprises the following steps: Step 1: Substrate processing Step 1.1, use acetone to remove oil stains on the surface of the substrate, and use dilute hydrochloric acid to remove surface oxides; Step 1.2: After drying, the cleaned substrate in step 1.1 is polished to further remove the surface oxide film; Step 1.3, placing the substrate processed in step 1.2 in a vacuum drying oven and storing it at room temperature under vacuum conditions; Step 2: Preparation and application of solder paste Step 2.1, placing the carbon nanosphere @Ag core-shell material in a mortar, adding an organic dispersant, grinding it fully to make it evenly mixed and grinding it into a paste, to obtain a carbon nanosphere @Ag core-shell solder paste, wherein: the mass percentage of the mixed powder and the organic dispersant in the solder paste is 80-90%: 10-20%; Step 2.2, evenly coating the carbon nanosphere@Ag core-shell solder paste on the substrate processed in step 1 by screen printing; Step 2.3, place the substrate coated with solder paste in a constant temperature drying oven for preheating to remove some of the remaining anhydrous ethanol in the solder paste to avoid the formation of more pores in the sintered structure; Step 3: Hot pressing and sintering The chip is placed on the solder paste to form a sandwich structure and then put into a hot press for hot pressing and sintering.
5. The process for interconnecting the carbon nanosphere@Ag core-shell material according to claim 4, characterized in that The organic dispersant is one or a mixture of polyethylene glycol-400, ethanol, butanol, ethylene glycol and propylene glycol.
6. The process for interconnecting the carbon nanosphere@Ag core-shell material according to claim 4, characterized in that The coating thickness of the carbon nanosphere@Ag core-shell solder paste on the substrate is 50 to 200 μm.
7. The process for interconnecting the carbon nanosphere@Ag core-shell material according to claim 4, characterized in that The preheating temperature is 110-140°C and the preheating time is 5-30 minutes.
8. The process for interconnecting the carbon nanosphere@Ag core-shell material according to claim 4, characterized in that The heating method of the hot pressing sintering adopts double-sided heating, the temperature rise rate is 4-10°C / min, the pressure is 1-10 MPa, the heating temperature is 250-350°C, and the heating time is 5-60 min.
9. Application of the carbon nanosphere@Ag core-shell material prepared by the method according to any one of claims 1 to 3 in the field of electronic packaging micro-interconnection technology.
Citation Information
Patent Citations
Ultrahigh-specific-area hollow carbon nano-spheres as well as preparation method and application thereof
CN104591127A
Method for modifying surface of carbon nanotube with nanosilver, and application of nanosilver-modified carbon nanotube
CN110092369A
Preparation method and application of hollow carbon nanosphere confinement tin nanocluster composite material
CN112794305A
Micron In and nano Cu-coated Ag core-shell mixed material interconnection process
CN115410934A